Prevalence and predictors of resistant hypertension among out-patients in Ilorin, Nigeria - James Ayodele Ogunmodede; Olalekan Ayodele Agede (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
Introduction: Systemic hypertension (SH) contributes the highest number of deaths from cardiovascular diseases worldwide. Patients with resistant hypertension (RH) are more prone to hypertension-mediated organ damage. RH has not been well-studied in Africa, despite the fact that the prevalence of SH is highest in Africa. The aim of the study was to establish the prevalence and predictors of RH among out-patients managed in the cardiology unit of the University of Ilorin Teaching Hospital, Ilorin, Nigeria. Method: A cross-sectional study of 201 patients selected via systematic random sampling between April and September 2019. Results: Mean age of the participants was 59.6 (SD 13.8) years, females 58.7%, 32.3% were non-obese, 17 (8.5%) consumed alcohol and three (1.5%) smoked tobacco. 30 participants (14.9%) had co-morbid diabetes mellitus. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were significantly higher among patients with RH 152.5 (SD 18) mmHg vs 131.9 (SD 18.4) mmHg (p<0.001) and 89.43 (SD 13.8) mmHg vs 79.46 (SD 10.5) mmHg (p=0.008). Eighteen patients (8.96%, 95% CI: 5.5-14%) had RH. The predictors of RH were obesity (OR= 3.754; p=0.009), SBP at patients' first clinic visit, (OR=1.029, p=0.032), DBP at patients' first clinic visit, (OR=1.048, p=0.014), and serum phosphorus, (OR=1.047, p=0.047). Conclusion: The prevalence of RH among our patients is low and is similar to that in studies with similar blood pressure cut-off values and case definition.